Motivasi Kerja Karyawan PT XYZ - Tini Kartini; Suci Nuralita (Institut Nalanda, 2024)
Employee motivation is crucial to ensuring that every employee can work optimally. This study aims to identify the low levels of employee motivation at PT XYZ. The decline in motivation is caused by several issues, such as compensation that does not meet expectations and less harmonious working relationships. These factors have resulted in the company's targets not being achieved. The research method used is qualitative descriptive, with data collection methods including in-depth interviews, observations, literature studies, and documentation. The results of the study show that adequate compensation can increase employee motivation. Furthermore, harmonious working relationships can help employees complete their tasks effectively. This study recommends improving compensation policies and efforts to create a conducive working environment to enhance employee motivation, thereby enabling the company to achieve its targets.